Interactive Modules Based Adobe Director On Computer Assembling Subjects For Vocational Secondary School Students - Indra Wijaya; Rini Sefriani (VOLT : Jurnal Ilmiah Pendidikan Teknik Elektro, 2017)
This study aims to create an interactive learning module that qualifies valid, practical and effective for Computer Assembling subjects in Vocational High School.  This research is a Research and Development research conducted in Vocational High School class X  West Sumatra. The population of this research is SMK in West Sumatra. Samples are SMKN 6 Padang SMKN 1 Painan, SMKN 2 Pulau Punjung. The results of the assessment of the three validators overall validator test assessment of the Interactive Module of 88.67% so that the level of validity can be interpreted Valid used. Overall assessment of the practicality of the Interactive Module as a learning resource of 86.08%, so the level of practicality can be interpreted Very Practical used. And the effectiveness assessment of Interactive Module as learning resource equal to 85,25%, so the level of effectivity can be interpreted Highly Effective used.